Inovasi Digitalisasi UMKM Perempuan untuk Pengurangan Dampak Lingkungan di Balikpapan sebagai Wilayah Penyangga IKN Nusantara - Uni W. Sagena; Alrifda Salsabilah; Andini Fadelia; Azari Pradya Devi Shafira; M. Hasyim M; Mohd Dino Khairri Shariffuddin (Universitas Mataram, 2023)
Financial bookkeeping is one of the most important things in business and personal activities. However, in practice there are still many parties who have not done financial bookkeeping or are still doing the bookkeeping manually. Therefore, the DIGIKAS & IBUK Dual Program was carried out so that the target financial accounting process could run more easily, be more environmentally friendly (Paperless), and reduce the impact on the environment. The dual program was aimed to 60 UMKM in the Water Settlement Area, 70 participants consisting of Ibu PKK and RT Cadre in Kelurahan Marga Sari. The method used in the IBUK & DIGIKAS dual program are interview, socialization and practice (real action). The results of the activity are that UMKM in Marga Sari Village receive additional information and knowledge about the importance of financial bookkeeping, know the digital financial bookkeeping application,